Photoinduced synthesis of fluorinated dibenz[b, e]azepines via radical triggered cyclization. Issue 73 (16th August 2019) - Qi, Xu-Kuan; Zhang, Hong; Pan, Zi-Tong; Liang, Rong-Bin; Zhu, Can-Ming; Li, Jing-Hong; Tong, Qing-Xiao; Gao, Xue-Wang; Wu, Li-Zhu; Zhong, Jian-Ji
Abstract : A simple, mild and efficient approach to access fluorinated dibenz[ b, e ]azepines via visible-light photoredox catalysis is presented. Abstract : A simple, mild and efficient approach to access fluorinated dibenz[ b, e ]azepines via visible-light photoredox catalysis is presented. Inexpensive and commercially available fluoroalkyl anhydrides in concert with pyridine N -oxide are employed as the source of the fluoroalkyl radicals. A one-pot process involving the trifluoroacetylation of unprotected secondary benzyl amines followed by radical cyclization could also afford the desired fluorinated dibenz[ b, e ]azepines.